Estimation of Heat Energy in Regeneration of Agricultural Machine Parts by Welding Methods (Agricultural Engineering, 2020)
In the paper, the method of calculating the welding energy needed to regenerate parts of agricultural machines by welding (joining) or surfacing (rebuilding, hardfacing) is presented. Problems with the lack of adequacy of the commonly used formula for linear welding energy to the actual amount of heat introduced into the welded joint are discussed. A volumetric approach based on the effective amount of heat generated by the electric arc introduced per unit volume of the weld was proposed. The simplified formulas for volumetric energy are presented. The considerations are illustrated with examples of calculations. The analyzed examples include the use of a computerized stand for geometric measurements of metallographic specimens. The proposed volumetric method of calculating the amount of heat introduced into the welded joint is a more realistic indicator of heat demand than linear energy. On the other hand, based on the volume of the weld (padding weld), it allows to determine the amount of energy needed to regenerate machine parts, including agricultural ones.